A systematic review of the association of diet quality with the mental health of university students: implications in health education practice. Issue 1 (28th November 2022) - Solomou, Solomis; Logue, Jennifer; Reilly, Siobhan; Perez-Algorta, Guillermo
Abstract: University students are at risk of experiencing mental health problems during the transition from home to university. This transition can also adversely affect their diet quality. This review aims to examine bidirectional associations from observational studies regarding the influence of diet quality on the mental health of university students, and vice versa. The databases PubMed, CINAHL, EMBASE, PsycINFO, The Cochrane Library and Web of Science were searched using relevant search terms. The searches were last updated on 15 July 2022. Majority of studies (36 out of 45) found that good diet quality of students was associated with better mental health in terms of depression, anxiety, stress and overall general mental well-being. Moreover, majority of studies (19 out of 23) found that stress and anxiety of students were associated with poorer diet quality. The effect sizes observed were generally small–moderate. Healthy diets of students have been associated with better mental health in terms of depression, anxiety, stress or other mental health issues. Stress experienced by university students has been associated with unhealthy diets. There are implications for health education research, as interventions to improve diet quality at the university level could reduce mental health issues; additionally, interventions to support students under stress may lead to healthier dietary habits when living on campuses. Randomized controlled trials and intervention studies are needed to further investigate these implications.